Self-Management Status and COVID-19 Phobia of Patients with Type 2 Diabetes - Gunes Alkaya Feyizoglu and Berna Dincer (Professor Despina Sapountzi-Krepia, 2024)
Self-Management Status and COVID-19 Phobia of Patients with Type 2 Diabetes